Safety and efficacy of explanting or replacing suprachoroidal electrode arrays in a feline model. (10th October 2014) - Leung, Ronald T; Nayagam, David AX; Williams, Richard A; Allen, Penelope J; Salinas‐La Rosa, Cesar M; Luu, Chi D; Shivdasani, Mohit N; Ayton, Lauren N; Basa, Meri; Yeoh, Jonathan; Saunders, Alexia L; Shepherd, Robert K; et al.
Abstract Background A key requirement for retinal prostheses is the ability for safe removal or replacement. We examined whether suprachoroidal electrode arrays can be removed or replaced after implantation. Methods Suprachoroidal electrode arrays were unilaterally implanted into 13 adult felines. After 1 month, arrays were surgically explanted (n = 6), replaced (n = 5) or undisturbed (n = 2). The retina was assessed periodically using fundus photography and optical coherence tomography. Three months after the initial implantation, the function of replaced or undisturbed arrays was assessed by measuring the responses of the visual cortex to retinal electrical stimulation. The histopathology of tissues surrounding the implant was examined. Results Array explantation or replacement was successful in all cases. Fundus photography showed localized disruption to the tapetum lucidum near the implant's tip in seven subjects following implantation. Although optical coherence tomography showed localized retinal changes, there were no widespread statistically significant differences in the thickness of the retinal layers or choroid. The distance between the electrodes and retina increased after device replacement but returned to control values within eight weeks (P < 0.03). Staphylomas developed near the scleral wound in five animals after device explantation. Device replacement did not alter the cortical evoked potential threshold. Histopathology showed localized outer nuclear layer thinning, tapetal disruption and pseudo‐rosette formation, but the overall retinal morphology was preserved. Conclusions It is feasible to remove or replace conformable medical grade silicone electrode arrays implanted suprachoroidally. The scleral wound requires careful closure to minimize the risk of staphylomas.